Paradoxical Antidepressant Effects of Sleep Deprivation in Depression: Mechanisms, Clinical Effects, and Therapeutic Implications - Jaworski, Arkadiusz; Szyszka, Michał; Brzostek, Karolina; Sobieraj, Jakub; Lewicka, Wiktoria; Misiąg-Marmura, Weronika; Szaliński, Konrad; Soczomska, Pola; Stopa, Małgorzata; Sośniak, Izabella (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Sleep deprivation (SD), paradoxically, has been shown to induce rapid antidepressant effects in patients with depressive disorders. This review explores the neurobiological underpinnings, clinical efficacy, and therapeutic strategies involving SD, aiming to clarify the mechanisms responsible for its mood-elevating effects and to assess its role in modern treatment of depression. Description of the state of knowledge: Clinical evidence consistently shows that a single night of total or partial SD can lead to a rapid reduction in depressive symptoms in approximately 40–60% of patients. However, these effects are short-lived, with relapse typically occurring after recovery sleep. Combination therapies, such as SD with phase advance and bright light exposure, have been developed to prolong therapeutic benefits. On the neurobiological level, SD appears to act through multiple pathways: resetting dysregulated circadian rhythms, enhancing monoaminergic neurotransmission (particularly serotonin and dopamine), upregulating brain-derived neurotrophic factor (BDNF), and inducing synaptic plasticity. Acute activation of the hypothalamic–pituitary–adrenal axis and transient increases in inflammatory markers have also been observed, suggesting a complex physiological adaptation that accompanies mood improvement. Additionally, glial mechanisms involving adenosine signaling may contribute to the antidepressant response. Summary: Sleep deprivation represents a unique, non-pharmacological intervention capable of rapidly alleviating depressive symptoms. Although transient on its own, its combination with chronotherapeutic or pharmacological strategies offers promising avenues for sustained therapeutic effect. Insights from SD research deepen our understanding of depression’s neurobiology and support the development of fast-acting antidepressant treatments that target circadian and neuroplastic mechanisms.